2001
DOI: 10.4102/sajems.v4i2.3295
|View full text |Cite
|
Sign up to set email alerts
|

Some recommendations towards reducing electricity consumption in the South African manufacturing sector

Abstract: This paper investigates the means of reducing electricity consumption in the South African manufacturing sector. It concludes that neither the price of electricity, nor taxes, subsidies or legislation are likely to bring about the required change. A change in the production structure using relatively more labour and less capital is also unlikely in the immediate future, given the socioeconomic and legislative milieu currently prevailing in South Africa. The only feasible solution that seems likely is a change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The level of the electricity prices is historically very low, which has also a caused a lack of behavioural response to price changes, as Blignaut and De Wet (2001) point out. Moreover, the real prices in a number of sectors declined significantly until 2002, when the price reform began to take effect.…”
Section: Discussion: Policy Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of the electricity prices is historically very low, which has also a caused a lack of behavioural response to price changes, as Blignaut and De Wet (2001) point out. Moreover, the real prices in a number of sectors declined significantly until 2002, when the price reform began to take effect.…”
Section: Discussion: Policy Implicationsmentioning
confidence: 99%
“…Locally, Blignaut and de Wet (2001) examined the industrial electricity consumption with regard to the price by estimating the price elasticities for the various sectors between 1976 and 1996. They found weak relationships between electricity price and consumption, some of which were positive.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Following these events, many researchers have tried to detach the behaviour of consumers and their reactionsif any -to the past and also to future changes in tariffs. 3,[6][7][8][9] When these studies were published, the available data included information only up to 2007/2008 -a time when electricity tariffs were at historically low levels. 3 Hence, the data did not allow for the investigation of the possible impacts of price restructuring beyond 2007/2008 on the South African electricity market nor for any changes in elasticities.…”
Section: Introductionmentioning
confidence: 99%
“…The price elasticities of electricity demand, as well as government price setting regulations, will also influence the extent to which the tax burden can be shifted to end-consumers. Blignaut and De Wet (2001) calculated the arc price elasticity of electricity demand to investigate the effect of a change in the price of electricity on the consumption of energy over a twenty-year time period in South Africa. They reported that the manufacturing sector is relatively price inelastic in its decision making process.…”
Section: Electricity Generation Tax: Some Evidencementioning
confidence: 99%